New species of Metadesmolaimus and Stephanolaimus (Nematoda: Chromadoria) from Northern Ireland with reviews of the genera - Platt, H. M. (Zool. J. Linn. Soc., 1983)
Locality: NA; Cabinet:
NeMys doc_id: 7363